An investigation of factors affecting the interaction of CO2 and CH4 on shale in Appalachian Basin. (June 2016) - Hong, Lei; Jain, Jinesh; Romanov, Vyacheslav; Lopano, Christina; Disenhof, Corinne; Goodman, Angela; Hedges, Sheila; Soeder, Daniel; Sanguinito, Sean; Dilmore, Robert
Highlights: This paper investigates the interaction of CO2 and CH4 with Marcellus Shale samples. Adsorption capacities of both CO2 and CH4 showed linear relationships with TOC. Comparatively CO2 exhibited consistently higher adsorption capacities than CH4 . At TOC >2% adsorption capacity ratios of CO2 over CH4 were between 1.3 and 1.9. These capacity ratios are close to the ratio of critical temperatures between CO2 and CH4 . Abstract: Depleted unconventional gas reservoirs have been proposed reservoirs for long-term storage of anthropogenic CO2 . The injection of CO2 in such reservoirs may benefit from, (1) the presence of existing infrastructure and right-of-way to reduce sequestration costs, (2) the presence of an existing network of fractures to increase reservoir contact efficiency, and (3) potential to enhanced gas recovery using CO2 . However, there remain significant technical challenges and uncertainties about the behavior of these reservoirs, and how they might respond to CO2 flooding. Toward addressing those uncertainties, the present study considers results of select experiments intended to improve understanding of the fundamental characteristics of shale matrix and shale interactions with methane and carbon dioxide. Outcrop samples from the low permeability sedimentary Marcellus formations in the Appalachian Basin of the eastern United States were characterized using various analytical techniques, including FTIR, XRD, ICP-OES, TOC analyzer, surface analysis, and pycnometry. FTIR confirmed CO2 adsorption by appearance of an absorption band near 2349 cm −1, however, CH4 absorption band at 1303 cm −1 was comparatively weak. Total organic carbon (TOC) exhibits significant statistical correlation with Cu, K, and Ni, while several other metals (As, Ba, Ca, Cd, Co, Cr, Fe, Mg, Mn, Na, Sr, and Ti) correlated with total inorganic carbon (TIC). Shale adsorption capacities of both CO2 and CH4 showed linear relationships to the organic matter content with CO2 exhibiting consistently higher adsorption capacities than CH4 . At organic matter content greater than 2 wt%, the ratios of adsorption capacity of CO2 over CH4 were in a range between 1.3 and 1.9, which is similar to the ratios of critical temperatures between CO2 and CH4 . This study evaluates the role of various physical and chemical parameters on CO2 /shale and CH4 /shale interaction, and considers implications for sequestration of CO2 in depleted shale reservoirs.